A phytotoxicity assessment of the efficiency 2,4-D degradation by different oxidative processes - Forti, Juliane C. [UNESP]; Loretti, Gustavo H. [UNESP]; Tadayozzi, Yasmin S. [UNESP]; de Andrade, Adalgisa R. [UNESP] (Elsevier, 2020)
Highly stable compounds such as dichlorophenoxyacetic acid (2,4-D), which are present in the commercial herbicide Tordon®, are difficult to degrade. Therefore, the objective of this work was to degrade 2,4-D present in Tordon® using different oxidative processes, such as anodic oxidation, Fenton reactions, electro-Fenton, photoelectro-oxidation and photoelectro-Fenton processes. An oxide electrode with the nominal composition Ti/Ru0.3Ti0.7O2 was prepared and inserted into an electrochemical cell containing 100 mL of 0.05 mol L−1 Na2SO4 (pH 3) and 100 mg L−1 of Tordon®. Electrolysis was performed applying a constant current of 50 mA cm−2 for 2 h. The concentration of Fenton's reagent was varied from 5 to 10 mg L−1 (Fe2+), and from 50 to 100 mg L−1 (H2O2). Chemical analyses of the total organic carbon (TOC) and the chemical oxygen demand (COD) were performed whilst high-performance liquid chromatography (HPLC) was used to monitor the degradation. A phytotoxicity assessment was performed using cucumber seeds as bioindicators. Germination tests were performed using cucumber seeds in the presence of the solutions collected after the application of the oxidative processes. Several analyses were carried out to determine the following: total protein content, the extent of lipid peroxidation, activity of superoxide dismutase, hydrogen peroxide content, catalase activity, and glutathione reductase activity. Oxidation of 2,4-D was observed in all of the oxidative processes, and significant results for the removal of TOC and COD were obtained. Anodic oxidation, and the Fenton and photoelectro-oxidation processes were the least efficient, affording 2,4-dichlorophenol, 2-chlorohydroquinone, and 2-chlorobenzoquinone as by-products. The electro-Fenton and photoelectro-Fenton processes were the most efficient, giving short-chain acids as the main by-products. The formation of these by-products directly affected the phytotoxicity results. The processes that formed short-chain by-products did not generate significant oxidative stress during seed growth, and therefore, seed germination tests were successful.
Keywords: 2,4-D; Cucumber seeds; Environmental treatment; Oxidative processes; Phytotoxicity assessment; Tordon®